A Decision Phases of a Supply Chain Management : A Proposed Decision Support System to Boost Organizational Decision Making - D.K. Attadjei, Desmond; Madhwal, Yash; Peter B. Panfilov, Dr (International Journal of Engineering and Technology, 2018)
A powerful and effective store network administration sires, a smooth running of a business, quality items or potential benefits, consequently escalating client trust and business picks up. To land at this phase in an association's business outgrowth, all rely upon the best choices that must be taken to move the correct way. These choices are normally aftereffects of past events and outside information that have been incorporated to give data or learning. For this reason, a decision support system is hereby proposed to be able to pool data from the 3 main decision phases of a Supply Chain Management, namely: (1) supply chain design (Strategy) phase, (2) decision in supply chain management (Planning) phase, and (3) operational level (Operation) phase. This proposed framework is pointed and boosting basic leadership process, by giving brought together data to help the hierarchical basic leadership process.Â